The life history approach: Fieldwork experience - Noor Rahamah Hj. Abu Bakar,; Mohd. Yusof Hj. Abdullah, (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2008)
Life history approach in qualitative research emphasises on the importance of presenting the individual‟s subjective evaluation of his experiences and of giving information about his social experiences. It is the account of a life, completed or ongoing. This approach combines both written and oral evidence. The information gathered offer basic evidence about social interaction and process. There are many problems involved in the use of life history approach such as reliability, validity and interpretation of information. However, it has certain advantages for studies of social change, as documentation on roles, demonstration of socialisation, and as a mean towards understanding variation within a society. At one time special attention was given to the use of life history approach but not much recording and analysis had been done. Perhaps because researchers have not been very clear about what to do with a life history narrative. The researchers‟ effect upon the research process and the analysis seems to be a concern in contemporary qualitative research. The same is also true about the individuals, their attitudes and understanding about the subject matter. This article attempts to highlight these key issues. The focus of discussion are on the attitudes of the researchers and his/her roles as a communicator in conducting research. Therefore, the objective of this paper is to discuss the conceptual aspect of life history approach and to identify the strategies used by researchers to effectively communicate with the individual in the process of collecting information